Modelling suicide ideation from beep to beep: Application of network analysis to ecological momentary assessment data - Rath, Dajana (Internet Interv, 2019)
• EMA data were analyzed using network analysis (e.g., temporal networks). • Suicidal ideation at t was predicted by itself and perceived burdensomeness at t – 1. • Suicidal ideation at t − 1 predicted perceived burdensomeness, depression etc. at t. • At the same beep, suicidal ideation was related to all variables in the network. • Patients with higher average suicidal ideation had higher average hopelessness.